Analisis Keabsahan Pemecahan Sertifikat Hak Milik atas Tanah yang Masih Boedel Waris Tanpa Persetujuan Semua Ahli Waris (Studi Putusan Nomor 137/PDT.G/2023/PN MDN) - Silvin Aurelia; Hasim Purba; Sutiartono (Jurnal Hukum Lex Generalis, 2025)
Inheritance law is closely related to various aspects of human life, as every individual will inevitably encounter the legal event of death. Upon the death of a person, land ownership certificates forming part of the estate are transferred to the heirs. Heirs may initiate a name transfer and certificate splitting process if there are multiple heirs. This study is a normative juridical legal research with a descriptive nature. The research employs a statutory approach and a case approach. The data used is secondary data, consisting of primary, secondary, and tertiary legal materials. Data collection techniques involve literature study, and data collection tools include document review. The data gathered is analyzed qualitatively. The findings indicate that the splitting of land certificates inherited from the deceased can be legally valid without the consent of all heirs, provided there is a court ruling in which one of the heirs has filed a lawsuit. The legal consideration of the judges in case number 137/Pdt.G/2023/PN.Mdn essentially explains that the Panel of Judges ultimately granted the Plaintiffs’ claim in full and validated the splitting of the inherited land certificate, despite the absence of the Defendants’ signatures.